Discovery Learning Model Analysis In The Element Of Poetry Learning Plan - Dellia Kusuma Ningrum, Tri Mahajani, Stella Talitha, Suhendra (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
Learning Implementation Plan is a guideline for teachers so that the learning process in the classroom can be better directed. The Learning Implementation Plan is developed in detail from a subject matter or theme. The learning model is one of the components contained in the Learning Implementation Plan. The learning model used can make the learning atmosphere more interesting and can motivate students in the learning process. In this paper, the researcher will analyze the discovery learning model in the Learning Implementation Plan for the elements of poetry-building class X MA Islamiyah Ciputat. This analysis was conducted to determine the suitability of the steps of the learning model of discovery learning in the Learning Implementation Plan of the elements of poetry builder class X MA Islamiyah Ciputat. The study was conducted at two meetings contained in the Learning Implementation Plan. The method used in this study is a qualitative method. The qualitative research method uses triangulation (combined) techniques to collect a data. Data collection in this study was done by reading in the section that was made the focus and subfocus of the study. The data part that is used as focus and subfocus is the steps of discovery learning model. The validity of the findings analysis data was carried out by three triangulators. The purpose of this study, researchers can describe the suitability of the steps of discovery learning model learning. The results obtained and have been verified by three triangulators that analysis of the steps of the discovery learning model contained in the Learning Implementation Plan are appropriate. There are 52 data that have been obtained. But after the data was found, there was no poetry writing activity at the two meetings. At meeting one and meeting two only analyzed the elements of the poetry and editorials used at the same meeting one and two only replaced with learning material that will take place.